The Unmanned Killer Machine: The Proliferation of Armed Drones Technology, Strikes and Effects on International Humanitarian and Human Rights Laws (Global Journal of Human-Social Science, 2015)
With the advancement of technology, the shape and nature of warfare has changed. In recent times, there has been the proliferation of armed drones technology and its usage. From when drones were made operational in the Balkans war, they have been used particularly by the US in places like Afghanistan, Yemen, Somalia and Iraq and controlled by the CIA. With these rapid development and proliferations, machines are starting to take the place of humans in the battlefield. The proliferation and usage of these armed drones poses challenges to the principles of international humanitarian and human rights laws especially when they are operated by non-military personnel like the CIA, the parameters of their detention and prosecution. This paper therefore analyses the effects that the proliferation and usage of armed drones has on the basic principles of international humanitarian and human rights law and concludes that the ability of armed drones to carry out targeted killings without exercising effective control over territory and without having the individual in custody, threatens or presents dangers to the protection of life which is not only a concept of humanity but a human rights violation and posit also that innocent civilians can be killed and indeed have being killed in the process of their usage thence threatening the concept of distinction and proportionality which are some of the cardinal principles of 1HL and thence recommends that there should be the regulation in the manufacture, possession and usage of these weapons.